Two new species of Leptobatopsis Ashmead (Hymenoptera: Ichneumonidae: Banchinae) from South Korea and gynandromorphy in L. nigricapitis - Choi, Jin-Kyung; Kang, Gyu-Won; Lee, Jong-Wook (Zootaxa, 2015)
Four species of Leptobatopsis Ashmead are recorded for the first time from South Korea. Among them, L. koreana sp. nov. and L. daedeokensis sp. nov. are newly described. We also report two newly recorded species, L. nigricapitis Chandra & Gupta and L. appendiculata Momoi, from South Korea. In addition, we describe a case of gynandromorphy of L. nigricapitis in a single specimen from South Korea. This specimen presents bilateral asymmetry, with the left half of its habitus displaying male characters and the right half displaying female characters. We also provide a key to Eastern Palaearctic species of Leptobatopsis.